The characteristics of high-risk HPV-negative cervical cancer: a systematic review and meta-analysis - Lou, Jicheng; Guo, Feng (Frontiers in Oncology, 2024)
IntroductionIn order to comprehensive understanding of the characteristics of high-risk HPV-negative cervical cancer and aiming to provide certain evidence in the diagnosis and treatment of this kind of disease, the clinical and pathological characteristics of high-risk HPV-negative (hr-HPV-negative) cervical cancer was evaluated through systematic review and meta-analysis.MethodsWe employed a systematic search strategy incorporating both MeSH terms and free words across multiple databases including PubMed, Embase, Cochrane Library, Web of Science, CNKI and Wanfang. The strategy was specifically designed to identify articles investigating risk factors or clinical characteristics of hr-HPV-negative cervical cancer. Our database search spanned from their inception until October 2023. The literature selection and data collection processes were guided by predetermined inclusion and exclusion criteria. Each included research was independently evaluated by two reviewers using the Newcastle-Ottawa Scale (NOS) and a meta-analysis was conducted utilizing RevMan5.4.ResultsIn total, nine studies published between 2013 and 2020 were included. The risk of lymph node metastasis was notably higher in hr-HPV-negative cervical cancer patients compared to hr-HPV-positive counterparts [RR=1.99, 95%CI (1.46–2.72), P<0.0001]. It was found that clinical staging of Ib2 or higher grade was significantly increased in hr-HPV-negative cervical cancer patients, as reported by seven studies [RR=1.42, 95%CI (1.15–1.77), P=0.0001]. Non-squamous carcinoma incidence, reported in seven studies, was significantly higher in hr-HPV-negative patients [RR=2.56, 95%CI (1.63–4.01), P=0.001]. Adenocarcinoma incidence was also significantly higher in hr-HPV-negative cervical cancer patients [RR=2.36, 95%CI (1.44–3.89), P=0.005].ConclusionsCervical cancer patients not infected by hr-HPV exhibited increased rates of lymph node metastasis, adenocarcinoma, and non-squamous carcinoma. And they were often diagnosed at more advanced stages. These variables suggest that hr-HPV-negative cervical cancer patients presented with a more severe health status at the time of their initial cancer diagnosis.